التقبل التكنولوجي والشفقة بالذات وعلاقتهما بالاندماج الأكاديمي لدى عينة من طلاب كلية التربية: دراسة وصفية في ظل جائحة كورونا (COVID-19) - محمد، أحمد بكر قطب (جامعة المنيا - كلية التربية, 2021)
هدف البحث الحالي إلى تعرف مستوى التقبل التكنولوجي والشفقة بالذات والاندماج الأكاديمي، وتعرف الفروق بين مرتفعي ومنخفضي التقبل التكنولوجي والشفقة بالذات للطلاب في الاندماج الأكاديمي، وتعرف تأثير كل من: النوع، والتخصص الدراسي، ومحل الإقامة، والتفاعل بينهم في كل من: التقبل التكنولوجي والشفقة بالذات والاندماج الأكاديمي، وبحث إمكانية التنبؤ بالاندماج الأكاديمي للطلاب من خلال درجاتهم في متغيري التقبل التكنولوجي والشفقة بالذات، وأجري البحث على عينة أساسية من 500 طالباً بالفرقة الثانية بكلية التربية جامعة المنيا بمتوسط عمر زمني (17,67) وانحراف معياري (0.543)، وذلك في العام الجامعي 2020-2021 م، وتم اختيارهم بالطريقة عشوائياً، وقد استخدم الباحث المنهج الوصفي الارتباطي المقارن، وتم تطبيق 3 مقاييس هم: مقياس التقبل التكنولوجي في ضوء نموذج (Davis, 1989)؛ ومقياس الشفقة بالذات في ضوء نموذج (Neff, 2003)؛ ومقياس الاندماج الأكاديمي في ضوء نموذج (Shaufeli, et al., 2002)، وتوصل البحث إلى عدة نتائج أهمها: وجود مستوى متوسط في بعدي (الفائدة والمنفعة المتوقعة، الاستخدام الفعلي الحقيقي) للتقبل التكنولوجي، ووجود مستوى منخفض في بعدي (سهولة الاستخدام المتوقعة، الاتجاه والميل نحو الاستخدام) والدرجة الكلية للتقبل التكنولوجي، ووجود مستوى مرتفع في الشفقة بالذات، ووجود مستوى متوسط في بعدي (الحيوية، الاستغراق) للاندماج الأكاديمي، ووجود مستوى منخفض في بعد (التفاني) والدرجة الكلية للاندماج الأكاديمي، ولم يوجد تأثير دال إحصائياً لكل من النوع، ومحل الإقامة، والتخصص والتفاعل بينهم في متغيرات البحث الثلاثة باستثناء وجود تأثير دال إحصائياً لكل من التخصص، والتفاعل بين النوع والتخصص في متغير التقبل التكنولوجي، ووجود تأثير للتخصص في متغير الشفقة بالذات، ووجود تأثير لمحل الإقامة في متغير الاندماج الأكاديمي، وتوجد فروق دالة إحصائياً بين متوسطي درجات طلاب منخفضي ومرتفعي التقبل التكنولوجي في أبعاد الاندماج الأكاديمي في اتجاه مرتفعي التقبل التكنولوجي، ولم توجد فروق دالة إحصائياً بين متوسطي درجات طلاب منخفضي ومرتفعي الشفقة بالذات في بعد (التفاني) وفي الدرجة الكلية للاندماج الأكاديمي، بينما وجدت فروق دالة إحصائياً بين متوسطي درجات طلاب منخفضي ومرتفعي الشفقة بالذات في بعدي (الحيوية، الاستغراق) في اتجاه منخفضي الشفقة بالذات، وأمكن التنبؤ بالاندماج الأكاديمي من خلال متغيرات (سهولة استخدام التكنولوجيا، ثم الاستخدام الفعلي للتكنولوجيا، ثم الاتجاه والميل نحو استخدام التكنولوجيا) على الترتيب بنسب اسهام مختلفة، وأن متغيرات (اللطف بالذات، اليقظة العقلية، والشفقة بالذات الكلي) يتوسطوا توسطاً جزئياً العلاقة بين التقبل التكنولوجي والاندماج الأكاديمي.
The aim of the current research is to identify the level of technological acceptance, self-compassion, and academic engagement. Also to identify the differences between high and low technological acceptance and self-compassion for students in academic engagement , and to identify the impact of: gender, academic specialization, and place of residence, and the interaction between them in all of: technological acceptance, compassion Specifically and academic engagement , and to investigate the possibility of predicting students’ academic engagement through their scores in the variables both of technological acceptance and self-compassion. The research was conducted on a basic research sample of (500) students in the second year of the Faculty of Education, Minia University, with an average age of (17.67) and a standard deviation (0,543), in the academic year 2020-2021, and they were selected randomly. The researcher used the Descriptive correlative comparative method and applied 3 scales: technological acceptance scale in the light of the model (Davis, 1989); and the measure of pity in particular in the light of the model (Neff, 2003); And the academic engagement scale in the light of the model (Shaufeli, et al., 2002). The research reached several results, the most important are: a medium level in two dimensions (expected benefit and profit and real actual use) of technological acceptance, and a low level in two dimensions (expected ease of use, tendency and inclination to use) and the total degree of technological acceptance, and a high level of self-compassion and a medium level in the dimensions of (vitality, engagement) of academic engagement , and a slightly low level in the dimension of (dedication) and the total degree of academic engagement among the research sample members. Also, there was no statistically significant effect of gender, place of residence, specialization and the interaction between them in the three research variables except for a statistically significant effect of specialization, and the interaction between gender and specialization in the variable of technological acceptance, and an effect of specialization in the variable of self-compassion, as well as an effect of residence in the academic engagement variable, and there are statistically significant differences between the average scores of students with low and high technological acceptance in the dimensions of academic engagement in the direction of high technological acceptance. Moreover, there were no statistically significant differences between the average scores of low and high self-compassion students in the (dedication) dimension and the total degree of academic engagement , while there were statistically significant differences between the mean scores of low and high self-compassion students in the dimensions (vitality, engagement) in the direction of low self-compassion. Hence the researcher could predict the academic engagement through the variables of (ease of use of technology, actual use of technology, and tendency to use technology) respectively, with different contribution percentages, and that the variables (self-kindness, mindfulness, and total self-compassion) partially mediate the relationship between technological acceptance and academic engagement.
Keywords: التعليم الإلكتروني -- فيروس كورونا "كوفيد-19" -- الاندماج الأكاديمي -- طلبة الجامعات